Three zones fix all? Analyzing static welfare impacts of splitting the German bidding zone under friction - Berit Hanna Czock (Institute of Energy Economics at the University of Cologne (EWI), 2025)
This study examines the static market and welfare effects of splitting the German bidding zone, comparing a two-zone and a three-zone configuration for a 2030 scenario. Using a state-of-the-art grid and market model with explicit representation of frictions in flow-based market coupling and redispatch, the analysis finds that the investigated two-zone split results in a 1.6% static welfare loss as redispatch cost savings do not overcompensate the negative effect of more transmission constraints in the electricity market. Contrarily, three zones lead to a 4.4% static welfare gain, as redispatch cost decrease further than with two zones and trade between German zones is enhanced due to a reduction of loop flows on interconnectors between Germany's North and South. However, both bidding zone split options lead to significant distributional effects, with higher consumer costs and increased subsidy expenditures for renewable energy sources (RES), though these effects are less pronounced with three zones. Additionally, welfare effects are sensitive to scenario definition and representation of frictions. All in all, policymakers should carefully assess the uncertain welfare gains against the transition costs of a bidding zone split, while also considering distribution effects and interactions with existing policies such as the RES subsidy scheme. Reducing frictions in redispatch, albeit with new coordination challenges, could potentially achieve similar objectives with lower transaction costs and fewer distributional impacts.
Keywords: D47; D61; C61; Q40; 330; Market Design; Electricity Markets; Nodal Pricing; Energy System Modeling; Renewable Energies; Bidding Zones